Mitochondrial Complex V α Subunit Is Critical for Candida albicans Pathogenicity through Modulating Multiple Virulence Properties - Li, Shui-Xiu; Song, Yan-Jun; Zhang, Yi-Shan; Wu, Hao-Tian; Guo, Hui; Zhu, Kun-Ju; Li, Dong-Mei; Zhang, Hong (Frontiers in Microbiology, 2017)
The α subunit (ATP1) is a vital component of mitochondrial complex V which counts for the majority of cellular ATP production in a living organism. Nevertheless, how the α subunit influences other cellular processes such as pathogenicity in Candida albicans remains poorly understood. To address this question, ATP1 mutant (atp1Δ/Δ) and the gene-reconstituted strain (atp1Δ/ATP1) have been constructed in this study and their pathogenicity-related traits are compared to those of wild type (WT). In a murine model of disseminated candidiasis, atp1Δ/Δ infected mice have a significantly higher survival rate and experience a lower fungal burden in tissues. In in vitro studies atp1Δ/Δ lose a capability to damage or destroy macrophages and endothelial cells. Furthermore, atp1Δ/Δ is not able to grow under either glucose-denial conditions or high H2O2 conditions, both of which are associated with the potency of the macrophages to kill C. albicans. Defects in filamentation and biofilm formation may impair the ability of atp1Δ/Δ to penetrate host cells and establish robust colonies in the host tissues. In concert with these pathogenic features, intracellular ATP levels of atp1Δ/Δ can drop to 1/3 of WT level. These results indicate that the α subunit of Complex V play important roles in C. albicans pathogenicity.